Prior business experience, entrepreneurial intentions, and intention implementation among refugees: an application of the theory of planned behavior - Mabunda Baluku, Martin; Nansubuga, Florence; Wambi, Eria; Nyende, Paul; Nantamu, Simon (Springer Berlin Heidelberg, 2026)
Abstract Although refugees are often perceived as a burden to the socioeconomic fabric in some places, entrepreneurship offers a promising avenue for refugees to participate in the economy, secure decent work, and achieve self-reliance. However, refugee entrepreneurship is largely seen as necessity-driven and thus limited personal agency in refugees’ entrepreneurial behavior, which has negative connotations for persistence and success. This paper demonstrates the role of prior entrepreneurial experience in boosting refugees’ personal entrepreneurial agency (represented by entrepreneurial intentions and implementation intentions) through its effects on the antecedents specified in the theory of planned behavior (TPB). The study uses survey data from 404 refugees in Uganda. The participants were drawn from three large refugee settlements. A serial mediation analysis was conducted using PROCESS Macro in SPSS. The results indicate prior entrepreneurial experience positively predicts the TPB antecedent variables, suggesting that entrepreneurial experience is essential for a positive entrepreneurial attitude, subjective norm, and a strong perceived behavioral control (PBC) among refugees. These TPB antecedent variables mediated the effects of prior entrepreneurial experience on entrepreneurial intentions and implementation intentions. Significant double mediation paths were mainly observed via entrepreneurial attitudes and intentions, as well as via perceived behavioral control and entrepreneurial intentions. The results indicate that prior experience is a vital resource that can be a foundation for successful refugee entrepreneurship promotion. Thus, active learning approaches that boost experience acquisition can be useful in entrepreneurship training and education interventions. Arrangements such as innovation hubs, apprenticeships, and internships for refugees can be vehicles for active and experiential learning. The study extends the TPB by integrating prior experience as an antecedent of entrepreneurial attitudes, subjective norm, PBC, and implementation intention.
Keywords: Entrepreneurial attitudes; Entrepreneurial experience; Entrepreneurial intentions; Implementation intentions; Perceived behavioral control; Refugees; Subjective norm; Theory of planned behavior